Pengaruh Model Pembelajaran TGT Berbantuan Flipbook Interaktif Terhadap Hasil Belajar Siswa Kelas XI SMA - nurhafiza nurhafiza; Kurnia Ningsih; Titin Titin (Universitas Majalengka, 2019)
The research work aimed to find out the effect of cooperative model type teams games tournament on the student’s achievement of Senior High School Taruna Bumi Khatulistiwa in grade XI in structure and function cell in the reproductive system. The research was quasi experimental design using nonequivalent control group design. Sampel was collected using saturation sampling, grade XI Science 1 as the experimental class and grade XI Science 2 as the control class. The instrument consisted of 20 multiple choice questions. The research finding showed that the average score of student’s achievement for the experimental class was 16,50 and for the contorl class was 14,61. Based on t test, the research obtained tcount > ttable (2,91 > 1,69). This meant that there was a significant differences between student’s achievement using cooperative model type teams games tournament with convensional model. The effect size score was 0,71 with medium category gave big influence by 26,11%.